APPLICATION OF STOCHASTIC DIFFERENTIAL EQUATION WITH TIME-DELAY FOR EPIDEMIC SIS MODEL - TUSTIANA (NIM :10108030 ); Pembimbing : Dr. Agus Yodi Gunawan, VITA
In this final project, we shall deal with the application of stochastic differential equation with delay to the epidemic SIS model. We derive the stochastic model from the deterministic model by considering the probability of all possibles changing in the population. Since the infected population needs time to recover, we also include the time-delay into the model. We end up with the numerical simulation for the stochastic and delay model. Results show that the time-delay play an important role in determining the behavior of the solution : oscillatory or non-oscillatory.